2015
DOI: 10.4103/0975-7406.148742
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Candida activity of Quercus infectoria gall extracts against Candida species

Abstract: Background:Galls of Quercus infectoria have been traditionally used to treat common ailments, including yeast infections caused by Candida species.Objective:This study aimed to evaluate the in vitro anti-Candida activity of Q. infectoria gall extracts against selected Candida species.Materials and Methods:Methanol and aqueous extracts of Q. infectoria galls were tested for anti-Candida activity against Candida albicans, Candida krusei, Candida glabrata, Candida parapsilosis and Candida tropicalis. The minimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 24 publications
3
46
1
1
Order By: Relevance
“…The results indicated that the QI gall methanolic extract was bactericidal or fungicidal against the tested microorganisms. Similar findings were obtained from previous studies performed on the QI gall methanolic extract tested against urogenital pathogens (Nur Saeida et al, 2014;Baharuddin et al, 2015). The QI gall extracts is well known to have broad spectrum antimicrobial activities.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results indicated that the QI gall methanolic extract was bactericidal or fungicidal against the tested microorganisms. Similar findings were obtained from previous studies performed on the QI gall methanolic extract tested against urogenital pathogens (Nur Saeida et al, 2014;Baharuddin et al, 2015). The QI gall extracts is well known to have broad spectrum antimicrobial activities.…”
Section: Discussionsupporting
confidence: 89%
“…High total tannin content in the QI gall extract suggests it may be responsible for the antimicrobial properties against several microorganisms (Darogha, 2009;Hassan, 2011). The source of QI galls used in this study were as those used in the previous studies (Nur Saeida et al, 2014;Baharuddin et al, 2015) and they have been tested phytochemically for the presence of major polyphenols namely 1,2,3-benzenetriol or pyrogallol. The hydroxyl groups and alpha-beta double bonds in the phenolic compound contributes to the activities of killing or inhibiting the microbial growth by interfering with the cell wall or cell membrane biosynthesis (Akiyama et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies indicated that QI galls have a variety of pharmacological properties including being an astringent (Dar et al 1976), antidiabetic (Kaur et al 2007), antitremorine local anesthetic, antiviral (Harborne 1986), potential antibacterial (Hwang et al 2000), antifungal (Baharuddin et al 2015;Magbool et al 2018), larvicidal (Ikram & Nowshad 1977) and anti-inflammation (Mc Clure 1975;Muhamad & Mustafa 1994). Various types of QI extracts were reported to poses anticancer activity on cervical cancer cells (Hasmah et al 2010) and colon cancer cells (Roshni & Ramesh 2013).…”
mentioning
confidence: 99%
“…17 One of the potential plants found in Indonesia is Manjakani seeds (Quercus infectory Gall). [17][18][19][20][21] The seeds have the same ability as other herbal ingredients, and even have a broader ability than some other herbal ingredients. They are popularly carried out to maintain the area of female sex organs and commonly used in dosage form capsules, powders, jelly, sticks or decoction.…”
Section: Introductionmentioning
confidence: 99%